Association Between Cyberbullying Exposure and Suicide Risk Among Undergraduate Students: A Cross-Sectional Study - Hidayati, Laili Nur; Anggelica, Dhella; Sarkarsi, Rosnani Binti (Journal of Applied Nursing and Health, 2026)
Background: The increasing use of the internet and social media among undergraduate students has contributed to the growing prevalence of cyberbullying. Exposure to cyberbullying may negatively affect students’ mental health and increase the risk of suicidal ideation and suicidal behavior. However, limited evidence exists regarding the relationship between cyberbullying and suicide risk among college students in low- and middle- income countries, including Indonesia. Therefore, this study aimed to examine the relationship between cyberbullying exposure and suicide risk among undergraduate students. Methods: This cross-sectional study followed the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines and involved 392 undergraduate students recruited via convenience sampling. Cyberbullying exposure was treated as the independent variable, while suicide risk was the dependent variable. Data were collected using the Cyberbullying Behavioral Scale and the Beck Scale for Suicide Ideation (BSS). Statistical analysis was performed using the Spearman rank correlation test. Results: Most respondents reported low levels of cyberbullying exposure, 359 (91.6%), and low suicide risk (82.7%). Spearman rank analysis demonstrated a statistically significant positive relationship between cyberbullying exposure and suicide risk (r= 0.141, p = 0.005), indicating a weak positive correlation. Conclusion: Cyberbullying exposure was associated with suicide risk among undergraduate students. However, this finding should be interpreted cautiously and not considered evidence of a causal relationship. These results highlight the importance of mental health screening, cyberbullying prevention, and suicide risk assessment programs within university settings.